When "Old Ladies" Meet: On Being Seen and Heard in a Lonely World. Issue 3 (2nd April 2020) - Richard, Annette; Brothers, Doris
ABSTRACT: This article explores the unique relationships that sometimes develop between aging women who become friends or analytic partners. Having endured – and, to some extent, triumphed over – the insults and injuries that attend being a woman in Western society, and being aware of the limited time that remains to them, these women are able to develop connections that are more open and loving than those they had previously known. The article also examines a number of relevant topics including Adam Philips' reframing of helplessness and vulnerability as not only a curse but also a blessing, Mark Freeman's concept of narrative foreclosure and the effects of what Jill Stauffer terms "ethical loneliness." Two clinical vignettes are provided by way of illustration.